2017
DOI: 10.1039/c6ob02749k
|View full text |Cite
|
Sign up to set email alerts
|

Divergent synthesis from reactions of 2-trifluoromethyl-1,3-conjugated enynes with N-acetylated 2-aminomalonates

Abstract: A simple base mediated reaction of 2-trifluoromethyl-1,3-conjugated enynes with N-acetylated 2-aminomalonates was developed, which could deliver two distinct types of products depending on substrates, i.e. 4-trifluoromethyl pyrrolidine derivatives, or gem-difluoro-1,3-conjugated enyne derivatives. Various functionalized 4-(difluoromethylene)-1,2,3,4-tetrahydropyridines could be obtained in good yields via the gold(i)-catalysed 6-endo-dig cyclization of the corresponding gem-difluoro-1,3-conjugated enynes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Very recently, we reported a silver-catalyzed tandem intermolecular and intramolecular hydroamination reaction of 2-trifluoromethyl-1,3-enynes with primary amines, delivering various ring-trifluoromethylated 3-pyrrolines in good yields (Scheme ). During our mechanistic insight into this tandem reaction, we found that treatment of enyne 1a with benzylamine 2a (2.0 equiv) in chlorobenzene at room temperature in the absence of AgNO 3 catalyst for 45 h, both allenyl amine 3aa and homopropargylic amine 4aa were obtained in 41% and 26% isolated yield, respectively, along with recovery 28% of enyne 1a (eq ).…”
mentioning
confidence: 99%
“…Very recently, we reported a silver-catalyzed tandem intermolecular and intramolecular hydroamination reaction of 2-trifluoromethyl-1,3-enynes with primary amines, delivering various ring-trifluoromethylated 3-pyrrolines in good yields (Scheme ). During our mechanistic insight into this tandem reaction, we found that treatment of enyne 1a with benzylamine 2a (2.0 equiv) in chlorobenzene at room temperature in the absence of AgNO 3 catalyst for 45 h, both allenyl amine 3aa and homopropargylic amine 4aa were obtained in 41% and 26% isolated yield, respectively, along with recovery 28% of enyne 1a (eq ).…”
mentioning
confidence: 99%
“…Based on the obtained results and previous studies, plausible mechanisms for this reaction are proposed in Scheme . When DBU is used as the base, deprotonation of the 2-mercaptobenzimidazole 1 gives the nucleophilic bis -anion species Int I .…”
Section: Results and Discussionmentioning
confidence: 73%
“…For example, Xiao and coworkers demonstrated that β-CF 3 -1,3-enynes with a strong electron-deficient aromatic ring are less prone to undergo the defluorinative reaction pathway in the reaction with Nacetylated 2-aminomalonates. 15 With our continuing interest in trifluoromethyl alkenes, herein we disclose a base-controlled divergent cyclization of 2-mercaptobenzimidazoles and β-CF 3 -1,3-enynes, which could deliver trifluoromethylated and fluorinated benzo [4,5]imidazo [2,1-b][1,3]thiazines selectively by simply varying the base from DBU to KOH (Scheme 1B).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a gem -difluoroalkene is a versatile synthetic platform, which can be easily and efficiently transformed into other fluorinated skeletons, such as monofluoroalkenyl, 5 difluoromethylene 6 and trifluoromethyl. 7 Therefore, many useful methods including SN2′ reactions, 8 gem -difluoroolefinations 9 and allylic defluorinative cross-coupling reactions 10 have been established for the construction of gem -difluoroalkenes. Among them, the allylic defluorinative cross-coupling reaction has received considerable attention because of its easily available starting materials, mild conditions, high efficiency, and good functionality tolerance.…”
mentioning
confidence: 99%